Codon usage pattern in human SPANX genes - Choudhury, Monisha Nath (Bioinformation, 2015)
Background: SPANX (sperm protein coupled with the nucleus in the X chromosome) genes play a crucial role in human spermatogenesis. Codon usage bias (CUB) is a well-known phenomenon that exists in many genomes and mainly determined by mutation and selection. CUB is species specific and a unique characteristic of a genome. Analysis of compositional features and codon usage pattern of SPANX genes in human has contributed to explore the molecular biology of this gene. In our current study, we have retrieved the sequences of different variants of SPANX gene from NCBI using accession number and a perl script was used to analyze the nucleotide composition and the parameters for codon usage bias. Results: Our results showed that codon usage bias is low as measured by codon bias index (CBI) and most of the GC ending codons were positively correlated with GC bias as indicated by GC3. That mutation pressure and natural selection affect the codon usage pattern were revealed by correspondence analysis (COA) and neutrality plot. Moreover, the neutrality plot further suggested that the role of natural selection is higher than mutation pressure on SPANX genes. Conclusions: The codon usage bias in SPANX genes is not very high and the role of natural selection dominates over mutation pressure in the codon usage of human SPANX genes.